2021
DOI: 10.1016/j.ijantimicag.2021.106324
|View full text |Cite
|
Sign up to set email alerts
|

Increased antimicrobial resistance during the COVID-19 pandemic

Abstract: In addition to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection itself, an increase in the incidence of antimicrobial resistance poses collateral damage to the current status of the coronavirus disease 2019 (COVID-19) pandemic. There has been a rapid increase in multidrug resistant organisms (MDROs), including extended-spectrum β-lactamases-producing Klebsiella pneumoniae , carbapenem-resistant New Delhi metallo-β-lactamase-producing Enterobacterales, Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
264
3
18

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(290 citation statements)
references
References 50 publications
5
264
3
18
Order By: Relevance
“…High empiric use of broad-spectrum antibiotics observed for COVID-19 patients is heightening concern that antibiotic overuse during the COVID-19 pandemic will exacerbate the problem of antimicrobial resistance in microorganisms of clinical significance into the future. ( 36 , 37 , 38 ) The review by Rawson et al found that 72% of COVID-19 patients had received antibacterial therapy and that recorded agents tended to be broad-spectrum antibiotics prescribed empirically in both critical and non-critical settings. ( 10 ) A meta-analysis by Langford and colleagues of 3,338 hospitalised and critical COVID-19 patients across 24 studies reported that a majority of COVID-19 patients received antibiotics (71.9%, 95% confidence interval (CI): 56.1-87.7%).…”
Section: Multi-drug Resistance and Antimicrobial Stewardshipmentioning
confidence: 99%
“…High empiric use of broad-spectrum antibiotics observed for COVID-19 patients is heightening concern that antibiotic overuse during the COVID-19 pandemic will exacerbate the problem of antimicrobial resistance in microorganisms of clinical significance into the future. ( 36 , 37 , 38 ) The review by Rawson et al found that 72% of COVID-19 patients had received antibacterial therapy and that recorded agents tended to be broad-spectrum antibiotics prescribed empirically in both critical and non-critical settings. ( 10 ) A meta-analysis by Langford and colleagues of 3,338 hospitalised and critical COVID-19 patients across 24 studies reported that a majority of COVID-19 patients received antibiotics (71.9%, 95% confidence interval (CI): 56.1-87.7%).…”
Section: Multi-drug Resistance and Antimicrobial Stewardshipmentioning
confidence: 99%
“…The current situation is such that most bacterial pathogens are resistant to the frontline drugs like carbapenems, imipenem, and vancomycin, etc. The ongoing global pandemic due to SARS-CoV-2 has also dramatically enhanced the use of several antibiotics to treat the secondary bacterial infections among the patients (Rawson et al 2020a , b ), the impact of which on the AMR will be required to be assessed in due course (Knight et al 2021 ; Lai et al 2021 ; Rawson et al 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these factors may contribute to further exacerbating the emergence of antimicrobial resistance [ 16 , 17 , 18 ], and the World Health Organization (WHO), to prevent this, issued guidance to discourage antibiotic therapy or prophylaxis for patients with mild or moderate COVID-19 symptoms unless there is a clinical indication of a bacterial infection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%